STRATEGI PEMBELAJARAN INKUIRI PAK REMAJA PEMUDA DALAM MENDORONG TOLERANSI DAN KETERBUKAAN DI ERA DIGITAL - Priskila Issak Benyamin; Andinata Prayogo; Dewi Sandiani Loupatty; Cindy Alisya Silooy (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Religious tolerance is something that must be echoed to promote an attitude of respect for others between religions in Indonesia. There are still many people who do not understand this, even though religious tolerance is very important to implement in everyday life. This research focuses on inquiry strategies in encouraging tolerance to grow, especially in Christian religious learning. Researchers used a library study method with a qualitative approach. Each data is presented in the form of words that contain information and discussion in this inquiry strategy. The results of this research found that this inquiry strategy can be applied in Christian religious education in schools, in order to foster an attitude of tolerance and openness for everyday life.